2021
DOI: 10.1515/ijmr-2020-8149
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterizations of metal ions doped barium strontium titanate (BST) nanomaterials for photocatalytic and electrical applications: A mini review

Abstract: The ferroelectric barium strontium titanate (Ba1-xSrxTiO3) is a homogeneous solid solution prepared from the mixture of barium titanate (BaTiO3), strontium titanate (SrTiO3) and titanium (IV) isopropoxide. Barium strontium titanate (BST) nanomaterials with improved permittivity and dielectric properties due to their nano-properties have attracted great interest for extensive and versatile applications as super capacitors, dielectrics, ceramics and catalysts. Introduction of metal ion dopants into the parent sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…[50] After the oxygen vacancy is further introduced, the band gap absorption edge still has a slight red shift to 407.9 nm. This preliminary shows that Sr doping and oxygen vacancy incorporation can affect the band structure of original BaTiO 3 , [39,51] thus affecting the utilization efficiency of sunlight. Figure 5b is the current response diagram of BaTiO 3 , Ba 0.7 Sr 0.3 TiO 3 and Ba 0.7 Sr 0.3 TiO 3-X under simulated sunlight.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…[50] After the oxygen vacancy is further introduced, the band gap absorption edge still has a slight red shift to 407.9 nm. This preliminary shows that Sr doping and oxygen vacancy incorporation can affect the band structure of original BaTiO 3 , [39,51] thus affecting the utilization efficiency of sunlight. Figure 5b is the current response diagram of BaTiO 3 , Ba 0.7 Sr 0.3 TiO 3 and Ba 0.7 Sr 0.3 TiO 3-X under simulated sunlight.…”
Section: Resultsmentioning
confidence: 80%
“…In Figure 3a and 3b, the peaks of Ba 3d of Ba 0.7 Sr 0.3 TiO 3 and Ba 0.7 Sr 0.3 TiO 3-X both appear at positions of 780.13 eV and 795.38 eV, and the peaks of Sr 3d both appear at positions of 132.93 eV and 134.53 eV, with no obvious change, which indicates that after the introduction of oxygen vacancies, the difference in the chemical state of Ba and Sr has little effect. [39] In Figure 3c, for Ti 4 + , it is found that Ti in BaTiO 3 is located at positions 458.13 eV and 463.58 eV, while Ti in Ba 0.7 Sr 0.3 TiO 3 and Ba 0.7 Sr 0.3 TiO 3-X is located 457.88 eV and 464.03 eV. After the introduction of oxygen vacancies, the binding energy position of Ti 2p is shifted.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Reports also clarifed that the parameters of dielectrics such as dielectric constant, dielectric loss, and leakage current do usually get afected by the synthesis technique, chemical content, microstructure, identity, and the amount of dopants added where acceptor (lower valance than A or B components) and donor (higher valance than A or B components) dopants efectively change the properties of BST nanomaterial [18,[48][49][50][51][52][53][54][55]. Acceptor ions easily substitute Ti at the B-site where a one-phase arrangement is formed that leads to extra ionization of dopants which results in the occurrence of vacancies as well as lattice irregularities [56,57]. Dopants generally alter the physicochemical as well as charge carrier characteristics of the BST due to the formation of oxygen vacancies.…”
Section: Efect Of Unidoping and Codoping On Dielectric Property Of Bs...mentioning
confidence: 99%
“…Additionally, emerging technologies that rely on the absorption of pollutants on a target-specific basis are particularly appealing because they address poor efficiency imposed by off-targeting. As a consequence, several studies have focused on integrating nanotechnology principles with the chemical and physical surface modification of NMs to obtain engineered NMs that can conquer several of the issues encountered during contamination remediation [27][28][29]. Some key challenges that must be considered when developing new NMs for environmental remediation include target-specific identification, facile and economical fabrication, non-toxic nature, biocompatible, reusability, and the ability for regeneration after use [30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%